The East Indonesia Mujahidin commandos : new faces, same ideology - Kumar Ramakrishna (2013)
The recent killings of militants belonging to the so-called East Indonesia Mujahidin Commandos point not to the rise of a brand new militant network, but rather, yet another "mutation" of the old Darul Islam separatist movement or "super-organism".